Ukuran Gigi dan Tonjol Carabelli - Herniyati Herniyati; RIna Sutjiati; Tecky Indriana (Faculty of Dentistry, Universitas Indonesia, 2015)
The investigation conducted to evaluate the relationships between the size of teeth and carabelli's cips from 120 students of the Favulty of Dentistry a average of age of 20 years. The data of the size teeth and the carabelli's cups of the first permanent upper molars were optained from the upper arch printing. In addition, corresponding measure meats were also mode is the mesio-distal and bucco palatal teeth. The scores of the carabelli's cups were based on the Dalberg's classification. The results showed that the number of the teeth which had score I with grooves were high (48; 40%), then followed by score 0 (the average of mesio palatal cups) Which comprised of 44 teeth (20%), score 3 (there were depressions shaped as a small "Y" alphabet) were 19 teeth (15,83%), score 5 (there were small cups), score 6 (three were medium cups), score 2 *there wer pits) and score 4 (there were depression shaped as big "Y" alphabet which each comprised of 12 teeth (10%); 7 teeth (5,83%); 6 teeth (5%) and 4 teeth (3,33%). None of the teeth had carabelli's cup with core 7 (there were cups with big size). The results of the measurements on mesio-distal and bucco palatal teeth were variable. The smallest mesio-distal and bucco-palatal teeth were 0,20 mm and the largest were 12,80 mm. In size showed that there was a significant relationship between the teeth size and carabelli's cups which the size of carabelli's cups was always in line the teeth size.